Perbedaan Persepsi Gender Pada Mantan Staf Profesional Kantor Akuntan Publik - Aditya, Elma Muncar (Jurnal Ilmu Ekonomi ASET, 2009)
The purpose of this research is to analyze the differences between theperception of male accounting firm alumni and female accounting firm alumni to theirexperience, accounting firm programs, and the possibility to hire their ex accountingfirm. The data were collected through questionaire and the research was tested to 90accounting firm alumni which is 63 male accounting firm alumni and 27 femaleaccounting firm alumni. The hipothesis is tested using independent sample t-test. Theresults of this research are there is no significant perception differences between maleand female accounting firm alumni to their experience (H1), there is no significantperception differences between male and female accounting firm alumni to the accountingfirm programs (H2), and there is significant perception differences between male andfemale accounting firm alumni to the possibility to hire their ex accounting firm (H3).Keywords : accounting firm alumni, gender, perception, independent sample t-test.